An integrated physiology and proteomics analysis reveals the response of wheat grain to low temperature stress during booting - Anmin Zhang; Zihong Li; Qirui Zhou; Jiawen Zhao; Yan Zhao; Mengting Zhao; Shangyu Ma; Yonghui Fan; Zhenglai Huang; Wenjing Zhang (Journal of Integrative Agriculture)
Low temperature (LT) in spring has become one of the principal abiotic stresses that restrict the growth and development of wheat. Diverse analyses were performed to investigate the mechanism underlying the response of wheat grain development to LT stress during booting. These included morphological observation, measurements of starch synthase activity, and determination of amylose and amylopectin content of wheat grain after exposure to treatment with LT during booting. Additionally, proteomic analysis was performed using tandem mass tags (TMT). Results showed that the plumpness of wheat grains decreased after LT stress. Moreover, the activities of sucrose synthase (SuS, EC 2.4.1.13) and ADP-glucose pyrophosphorylase (AGPase, EC 2.7.7.27) exhibited a significant reduction, leading to a significant reduction in the contents of amylose and amylopectin. A total of 509 differentially expressed proteins (DEPs) were identified by proteomics analysis. The Gene Ontology (GO) enrichment analysis showed that the protein difference multiple in the nutritional repository activity was the largest among the molecular functions, and the up-regulated seed storage protein (SSP) played an active role in the response of grains to LT stress and subsequent damage. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that LT stress reduced the expression of DEPs such as sucrose phosphate synthase (SPS), glucose-1-phosphate adenylyltransferase (glgC), and β-fructofuranosidase (FFase) in sucrose and starch metabolic pathways, thus affecting the synthesis of grain starch. In addition, many heat shock proteins (HSPs) were found in the protein processing in endoplasmic reticulum pathways, which can resist some damage caused by LT stress. These findings provide a new theoretical foundation for elucidating the underlying mechanism governing wheat yield development after exposure to LT stress in spring.